Pemberdayaan Kader Kesehatan dalam Deteksi Dini Gangguan Neuropaty pada Penderita DM di Desa Rasabou, Kecamatan Bolo, Kabupaten Bima - Kurniadi; Sukmawati (CV. CENDIKIA JENIUS INDONESIA, 2024)
Diabetes can lead to serious complications, one of which is neuropathy or nerve damage. This community service aims to enhance the knowledge of health cadres regarding the early detection of neuropathy disorders in diabetes mellitus. The methods employed include education through videos and booklets. The activities are divided into three phases: preparation, implementation, and monitoring, with the involvement of the partner, the village head, in gathering cadres and providing facilities for education. The activities took place in Rasabou Village, Bolo District, Bima Regency, in May 2024. The majority of health cadres are aged between 30 and 50 years, with high school as their highest education. Before the training, 12 cadres (70.6%) had a good understanding of diabetes. After the training, this number increased to 14 cadres (82.4%) with good knowledge. The conclusion indicates a significant improvement in the knowledge of health cadres following the education through lectures, videos, and simulations. The cadres showed high enthusiasm during the activities. It is recommended that future outreach methods be more interactive to enhance community understanding and participation in health programs.